Recognition and Measurement of Fixed Assets: (Case Study on Government Organizations in Lumajang) - Ria Meilan; Alwan Sri Kustono; Wahyu Agus Winarno (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This research is different from previous research, this research focuses on the process that forms a system in the application of recognition and measurement of fixed assets with the problems that follow based on the perspective of PSAP 07. This type of qualitative research is used in this study with a case study approach. Sources of data through interviews, documentation, and observations of asset officers and accounting officers within the Dinas Kesehatan and UPT Puskesmas of Lumajang Regency. The validity of the data using the triangulation technique. The results of the study indicate that the application of recognition and measurement of fixed assets based on the perspective of PSAP 07 is carried out by the system that has been formed in the organization. This system serves as the basis for employees who are responsible for managing fixed assets. A theoretical contribution to this research is to strengthen Institutional theory. The practical contribution is a recommendation for the government maintain the system that has been formed with the hope that the management of fixed assets in OPD will be of higher quality.